Mechanism of collisionless sound damping in dilute Bose gas with condensate - Slyusarenko, Yu.; Kruchkov, A. (Condensed Matter Physics, 2013)
We develop a microscopic theory of sound damping due to Landau mechanism in dilute gas with Bose condensate. It is based on the coupled evolution equations of the parameters describing the system. These equations have been derived in earlier works within a microscopic approach which employs the Peletminskii-Yatsenko reduced description method for quantum many-particle systems and Bogoliubov model for a weakly nonideal Bose gas with a separated condensate. The dispersion equations for sound oscillations were obtained by linearization of the mentioned evolution equations in the collisionless approximation. They were analyzed both analytically and numerically. The expressions for sound speed and decrement rate were obtained in high and low temperature limiting cases. We have shown that at low temperature the dependence of obtained quantities on temperature varies significantly from those one obtained by other authors in the semi-phenomenological approaches. Possible effects connected with non-analytic temperature dependence of dispersion characteristics of the system were also indicated. Побудовано мiкроскопiчну теорiю загасання звуку за механiзмом Ландау у розрiджених газах iз бозе-конденсатом. В основу теорiї було закладено пов’язанi рiвняння еволюцiї для парамерiв опису системи. Цi рiвняння було виведено у бiльш раннiх роботах у мiкроскопiчному пiдходi, що базується на використаннi методу скороченого опису квантових систем багатьох частинок (метод Пелетминського) та моделi Боголюбова для слабко неiдеального бозе-газу з видiленим конденсатом. Отримано рiвняння дисперсiї звукових коливань у системi, що вивчається, шляхом лiнеаризацiї зазначених рiвнянь еволюцiї у беззiткненнєвому наближеннi. Проведено аналiз рiвнянь дисперсiї, як чисельно, так i аналiтично. Одержано аналiтичнi вирази для швидкостi розповсюдження й коефiцiєнта поглинання звуку в розрiджених газах iз бозе-конденсатом у граничних випадках великих та малих температур. Нами продемонстровано, що в областi малих температур температурна залежнiсть знайдених величин суттєво вiдрiзняється вiд тих, що отриманi ранiше iншими авторами в напiвфеноменологiчних пiдходах. Вказано на можливi ефекти, пов’язанi з неаналiтичними залежностями дисперсiйних характеристик системи вiд температури.